Analysis of pigment composition of brown seaweeds collected from Panjang Island, Central Java, Indonesia - Heriyanto; Juliadiningtyas, Ayu Dita; Shioi, Yuzo; Limantara, Leenawaty; Brotosudarmo; Tatas Hardo Panintingjati (2017)
Composition of pigments from four species of brown seaweeds (Phaeophyceae) collected from Panjang Island, Central Java, Indonesia, was investigated with spectroscopic method and reverse-phase high-performance liquid chromatography (RP-HPLC). Identification of pigments was based on their spectral and chromatographic properties and also confirmed by electrospray ionization-mass spectrometry (ESI-MS/MS) analysis. The experimental results showed that concentrations of chlorophyll a (Chl a) and total carotenoids (Cars) from brown seaweeds, estimated by spectroscopic method, varied depending on species from 1.73 mg ? g?1 to 8.84 mg ? g?1 and from 0.55 mg ? g?1 to 4.06 mg ? g?1 dry weight (dw), respectively. In addition, the order of concentrations of Chl a and total Cars in four species of seaweed was as follows: Dictyota dentata > Padina australis > Sargassum crassifolium > Turbinaria conoides. This order was in agreement with the concentrations of dominant pigments calculated by HPLC method, i.e., fucoxanthin (Fuco) (0.43 mg ? g?1 to 4.11 mg ? g?1 dw), Chl a (1.70 mg ? g?1 to 7.89 mg ? g?1 dw), β-carotene (0.16 mg ? g?1 to 0.78 mg ? g?1 dw). These results suggest that D. dentata is likely potential source material to explore the industrial utilization, especially functional food and biomedical ingredients, of Fuco and Chl a. (Author's abstract)